Pengaruh Pendekatan Realistic Mathematics Education (Rme) Terhadap Peningkatan Pemahaman Konsep Matematis Siswa Kelas X Sma Negeri 2 Percut Sei Tuan - Pasaribu, Hana Sepania; Hia, Yasifati (Universitas Pakuan, 2026)
THE EFFECT OF THE REALISTIC MATHEMATICS EDUCATION (RME) APPROACH ON IMPROVING THE CONCEPTUAL UNDERSTANDING OF MATHEMATICS AMONG GRADE X STUDENTS OF SMA NEGERI 2 PERCUT SEI TUANThis study was designed to investigate the impact of implementing the Realistic Mathematics Education (RME) approach on the progress of Senior High School students’ ability to understand mathematical concepts. The research employed a quasi-experimental method with a Pretest-Posttest Control Group Design. The participants consisted of two classes: Class X-B as the experimental group, which received the intervention through the RME approach, and Class X-E as the control group, which was taught using traditional instructional methods. The instrument used was a mathematical concept understanding test, administered as a pretest before the intervention and a posttest afterward. The data obtained were analyzed using the Shapiro-Wilk normality test, homogeneity test, and Independent Sample t-Test. The findings revealed the following: (1) Students’ average pretest scores improved after the intervention, with the experimental group’s posttest scores outperforming those of the control group; (2) The t-test results indicated a significant difference between the two classes (Sig. 0.05); and (3) Consequently, the RME approach was proven to make a significant contribution to students’ understanding of mathematical concepts.